ANALYSIS OF FACTORS AFFECTING THE MOTIVATION OF THE YOUNG GENERATION TO WORK IN AGRICULTURE AT SEMARANG REGENCY AGRICULTURAL VOCATIONAL SCHOOL - Muhammad Taufiq Fahrurozi; Mukson Mukson; Wulan Sumekar (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
The decreasing number of young human resources in agriculture shows that the younger generation is less interested in working in agriculture. The continuation of this phenomenon can impact the food crisis due to the absence of humans who are willing to carry out agricultural cultivation. This study aims to analyze internal and external factors of the young generation of Agricultural Vocational School students, suspected to a construct of competence and motivation to work in agriculture. The research location is in the agricultural vocational school majoring in agribusiness of cash crops and horticulture in Semarang Regency, directly related to on-farm agricultural activities. To obtain qualitative data, the data collection method was carried out by distributing questionnaires to the XII grade students of agricultural vocational schools in Semarang Regency. The data were analyzed quantitatively using Partial Least Square (PLS) analysis. The results showed that family encouragement, support from educational institutions, farming skills, and job characteristics in agriculture significantly affected agricultural vocational students' competence in agriculture. Factors that significantly affect motivation to work in agriculture for vocational high school students are environmental factors, support from educational institutions, farming skills, characteristics of work in agriculture, and moral responsibility. Competence in agriculture has a significant effect on motivation to work in agriculture. Cooperation between families, schools, and communities is expected to increase the basis of the younger generation to work in the agricultural sector.